Os limites da categoria mulher no feminismo radical: uma contribuição psicanalítica para o debate de gênero - Monteiro, Laís Landes (2025)
Understanding gender as an imaginary and symbolic resource that attempts to account for the real at play in sexuality, the maintainance of a biologizing perspective for defining the category woman, within feminist thoughts, sounds essentialist and counterproductive. Assuming that certain experiences of socially structured oppression are exclusive to bodies of the female biological sex, radical feminism adopts a trans-exclusionary stance that can be problematized by other forms of knowledge. The current research aims to generate a psychoanalytic contribution to the gender debate by creating an interface between radical feminist discourse and Lacanian psychoanalysis, oriented towards the real of sex, beyond normative gender identities. Questioning the attachment to the category woman as something exclusive to the biological order, an analysis of the concept of gender socialization – drawing from radical feminism's take on Albert Bandura's Social Learning Theory – has been conducted. Through Lacanian psychoanalysis, moving from the theory of identification with the signifier in Seminar 9: Identification to the Lacanian theory of semblants and the critique of uniqueness, developed in the following decade in Seminar 18: From a Discourse That Was Not a Semblant and Seminar 19: ...Or Worse, and the theory of Lacanian sexuation formalized in Seminar 20: Encore, a critical literature review was outlined that opposes the epistemology of radical feminism. In light of this psychoanalytic perspective, the present bibliographic research concludes that neither the biological essencialism nor the social constructivism allow the foundation of the subject’s relationship with its sex.